Outcomes of mitral valve surgery for severe ischemic mitral regurgitation. Issue 2 (10th December 2019) - Dufendach, Keith; Aranda‐Michel, Edgar; Sultan, Ibrahim; Gleason, Thomas G.; Navid, Forozan; Thoma, Floyd; Kilic, Arman
Abstract: Background: This study evaluated outcomes of mitral valve surgery for severe ischemic mitral regurgitation (IMR). Methods: Patients undergoing coronary artery bypass grafting (CABG) with concomitant mitral valve repair (MVr) or replacement (MVR) for severe IMR at a single center between 2010 and 2017 were included. The primary outcome was 5‐year survival. Secondary outcomes included operative mortality and morbidity, hospital readmission, recurrence of at least moderate mitral regurgitation (MR), and mitral valve reoperation. Results: A total of 358 patients underwent concomitant mitral valve surgery with CABG for severe IMR (275 MVr and 83 MVR). Unadjusted and risk‐adjusted operative mortality was higher in MVR (16% vs 8%; P = .04). MVR patients had higher rates of postoperative renal failure, prolonged ventilation, and deep sternal wound infection. The unadjusted 5‐year survival was similar (MVR 64% vs MVr 64%; P = .41), a finding that persisted after risk‐adjustment. The 5‐year freedom from mitral valve reoperation was 96% and 97% ( P = .47). Freedom from at least moderate MR at 1‐year and 3‐years was 100% vs 86% ( P = .09) and 100% vs 68% ( P = .06) for MVR and MVr, respectively. However, only three MVr patients developed severe MR by 3 years. Cumulative hazards for all‐cause readmission and heart failure‐specific readmission were higher with MVR. Conclusions: Despite a trend towards higher risk of MR recurrence, patients undergoing MVr have similar rates of survival and mitral valve reoperation, with lower rates of readmission at 5‐years. This, combined with lower operative mortality rates, makes MVr a reasonable choice particularly in sicker patients with higher operative risk and more limited life expectancy.